TINGKAT SUKU BUNGA PINJAMAN DAN KINERJA KEUANGAN PERBANKAN: STUDI KASUS PADA BPR PT PRISMADANA - Sarah Usman (Jurnal Riset Manajemen dan Bisnis, 2011)
ABSTRACT The purpose of this study is to analyze the role of loan interest and its implication towards Rural Bank’s financial performance. Database collected from primer data is based on observation, meanwhile secondary data from Rural Bank’s financial statements during 2006-2008 period. This study based on net interest margin analysis. The role of loan interest and it’s implication proxied by net interest income indicator. This study shows that an increase in interest income (Net Interest Income) at Rural Bank due to an increase of it’s lending activities for five years. Thus, loan interest income has important role on the increasing perfomance of PT Prismadana rural bank's finance. Keywords: Interest Rate, Financial Performing, BPR